2016
DOI: 10.17234/socekol.25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Students' Attitudes and Behaviours in the Context of Environmental Issues

Abstract: Th e aim of this paper is to describe and analyse attitudes and behaviours of the student population (N=1347) of the University of Rijeka towards environmental issues. Data were collected during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This confirms the fourth hypothesis. The same results were obtained by Rončević and Cvetković (2016) and they concluded that students were most often involved in behaviours that were economically more profitable for them. Furthermore, Heyl, Diaz, Cifuentes (2013) found in the population of Chilean students that the most commonly practiced behaviours were those related to turning off the tap and turning off the lights, and the least related to buying recycled products due to the inability to afford them.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…This confirms the fourth hypothesis. The same results were obtained by Rončević and Cvetković (2016) and they concluded that students were most often involved in behaviours that were economically more profitable for them. Furthermore, Heyl, Diaz, Cifuentes (2013) found in the population of Chilean students that the most commonly practiced behaviours were those related to turning off the tap and turning off the lights, and the least related to buying recycled products due to the inability to afford them.…”
Section: Resultssupporting
confidence: 71%
“…No statistically significant difference was found on the other independent variables. Although some previous research found differences regarding to gender (Cifrić, 1997;Heyl, Diaz, Cifuentes, 2013;Rončević, Cvetković, 2016) in this study it was not possible to conduct statistical analyzes since gender was not relevant independent variable for further processing due to the predominance of female participants. Regarding to the results above, the last hypothesis is partially accepted.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, the results of previous studies in sustainability science point out to the presence of gender differences. Females express stronger positive attitudes towards sustainable development as well as higher level of willingness to act in environmental protection context and pro-ecological behavior, e.g., [61][62][63]. Bearing that in mind, it is possible that reasons due to which females are inclined to behave pro-sustainably may not replicate to males.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the results of previous empirical research indicate that the concern regarding the contribution to sustainable development as well as switching towards sustainable future differs depending on the individual's gender (Meinzen-Dick et al 2014). Therefore, women express stronger positive attitudes towards sustainable development as well as higher level of willingness to act in the direction of environmental protection and general pro-ecological behavior (e.g., De Silva and Pownall 2014;Rončević and Cvetković 2016). The abovementioned differences are also present in education for sustainable development and the student teacher area where it has been continuously found that female student teachers express more positive attitudes towards environment and ecological topics, higher level of ecological literacy, clearer conceptions regarding sustainable development topics as well as a higher level of awareness about burning questions related to sustainable development such as climate change (e.g., Al-Naqbi and Alshannag 2018; Kilinc and Aydin 2013;Larijani 2010;Oerke and Bogner 2010;Tuncer et al 2006Tuncer et al , 2009Vukelić 2021;Zelezny et al 2000).…”
Section: Socio-demographic Correlates Of Willingness To Act In Climate Change Mitigation and Adaptation Contextmentioning
confidence: 99%